Analisis Pengaruh Transparansi, Akuntabilitas, dan Peran Perangkat Desa terhadap Pengelolaan Dana Desa - Lita Yulita Fitriyani; Marita Marita; Windyastuti Windyastuti; Mustholihul Absor (Eksos LPPM, 2020)
This study aims to examine the influence of the variables Transparency, Accountability, and the Role of Village Officials on Village Fund Management in Kedewan District. This study uses a purposive sampling method with 30 respondents in five villages in Kedewan District. They are Kedewan district, Beji district, Hargomulyo district, Kawengan district and Wonocolo district. Data collection techniques in this study were in the form of questionnaires. The analysis used is multiple regression analysis using SPSS (Statistical Package for Social Science) version 20. The results of this study indicate that the variables Transparency, Accountability, and the Role of Village Officials affect the Village Fund Management variable.